Dehydration of isopropanol-water mixture by pervaporation using Y-type zeolite-filled chitosan membranes - 317402 So, Lea Kun (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Master of Engineering (Chemical)) - Universiti Teknologi Malaysia, 2004